(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article develops proposals in areas such as monitoring and management of water resources, precision technologies in irrigated agriculture, irrigation forecasting and optimization, development of intelligent farm management systems, and the use of data and analysis in decision-making in determining an integrated approach and strategic direction in digitalization of the water resources management system